Smart blinkers speed humps using solar panel - Ahmad Taqiyuddin, Mohamad (2019)
A speeding vehicle can be a menaced to other road users particularly on roads where interaction between motorized and non-motorized traffic is high, such as residential streets, school zones and community areas. Although speed limit signs are placed in accordance with the requirements of the standards, much is left to the conscience of the drivers whether they should abide by them. Hence, controlling vehicular speeds is a critical issue in traffic management. Physical speed reducing method such as speed hump is often used as one of the measures. Installation of speed humps at approaches to a junction will reduce speed, calm traffic and eventually provide safer crossing condition for all users. Since speed humps installed at junction of main entrance to UMP Gambang Campus are hardly visible at night, this study intends to equipped the speed humps with blinkers that will be solar powered. Pilot test using the speed humps with blinkers at nights indicated that vehicle speeds were reduced as compare to the scenario without the blinkers.